Public Preferences for Renewable Energy Options: A Choice Experiment in Rwanda - Oluoch, Sydney; Lal, Pankaj; Susaeta, Andres; Mugabo, Rodrigue; Masozera, Michel; Aridi, Jackline (Frontiers in Climate, 2022)
Rwanda has seen impressive economic growth in the past few years resulting from policy driven initiatives. However, one of the key challenges to economic development in Rwanda has been the provision of reliable and cost-effective energy. As a result, the country has planned to expand its renewable energy portfolio to meet its energy demand and mitigate greenhouse gas (GHG) emissions. Meeting these goals requires a robust policy framework that considers the perspective of the public. Moreso, for women who have been disproportionately affected by climate change especially in developing countries. Gender equality is a key for the Rwanda strategy as gender gaps remain a barrier to equal benefits from energy access to all. Several challenges abound in providing access to electricity and reducing the dependency on wood fuel for cooking, hence deliberate effort needs to be made to ensure gender responsiveness in energy programs and policies. This study applied a choice experiment analysis to determine how renewable energy attributes (type of energy, ownership, impact on environment, distance and visibility, community job creation and renewable energy tax) impacts public willingness to pay for renewable energy development in Rwanda. A nationwide survey was conducted on 1,006 households from which 58.35% were women. We applied both the conditional logit (MNL) and random parameter logit (RPL) framework. We found that the Rwandan public has a high utility for the following issues: environmental impact, distance and visibility, and type of renewable energy, respectively. Further analysis focused on the gendered impacts of renewable energy revealed that women had the strongest preference for interventions with low impact on the environment. From a policy standpoint women's input should be incorporated in future decision-making processes through public participation to guide policymakers in developing beneficial renewable energy programs.